ENHANCING PROFESSIONAL COMPETENCE OF VOCATIONAL TRAINING INSTRUCTORS IN UKRAINE AND EU COUNTRIES: GENERAL ASPECTS (Comparative Professional Pedagogy, 2024)
Vocational training serves as a cornerstone in equipping individuals with the necessary skills and knowledge for successful integration into the workforce. The competence of instructors tasked with imparting essential training is crucial for the effectiveness of vocational education. This article embarks on an extensive exploration into the realm of competence development within training programmes for vocational training instructors, focusing on the practices and methodologies employed in Ukraine, as well as prominent European Union (EU) nations such as Germany, Finland and the Netherlands. Drawing upon a synthesis of existing literature, the study meticulously examines the multifaceted challenges encountered by vocational training instructors. From outdated curricula to limited resources and inadequate professional development opportunities, the hurdles are diverse and complex. However, amid these challenges, the article offers a beacon of hope through actionable recommendations aimed at bolstering the professional competence of vocational training instructors. Noteworthy among these recommendations is the pivotal role of international partnerships and initiatives, which are instrumental in fostering collaboration and facilitating knowledge exchange to address the pressing issues faced by vocational training instructors. Moreover, the study delineates future research directions that hold promise for further enriching of the field. Longitudinal studies promise to provide invaluable insights into the sustained efficacy of development programmes for vocational training instructor over time. Comparative analyses across varied socio-economic contexts and educational systems offer a broader understanding of effective practices. Additionally, researches on the integration of technology stand poised to revolutionize instructor development, paving the way for innovative approaches and enhanced educational outcomes. Through this comprehensive exploration, the article not only sheds light on the challenges but also illuminates a pathway towards a more robust and dynamic vocational education opportunities.
Keywords: vocational training instructor; professional competence; Ukraine; European Union; professional development; international partnerships; comparative analysis